2015
DOI: 10.1155/2015/367217
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizers and Mixed Crop Cultivation of Chromium Tolerant and Sensitive Plants under Chromium Toxicity

Abstract: Zea mays (maize) and Vigna radiata (green gram) are found to be the chromium (Cr) tolerant and sensitive plants, respectively. In the present paper, we investigate the reduction of the toxicity of Cr in the sensitive plants by the mixed crop cultivation in the field using various amendments. Further, the potassium dichromate was used as the source of hexavalent Cr. The results indicated that Cr adversely affects both the growth and yield of plants. The soil properties vary with Cr and different fertilizer amen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…It ranged (48.03%) and (59.64%) in fresh weight and (46.455) and (56.47%) in dry weight respectively. The similar results reported by Dheeba et al (2015) who showed that salinity reduced the fresh and dry weight of plants. Deficiency in dry and fresh biomass at higher concentration might be due to poor absorption of water from the growth medium due to physiological drought (Ramezani et al, 2011).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It ranged (48.03%) and (59.64%) in fresh weight and (46.455) and (56.47%) in dry weight respectively. The similar results reported by Dheeba et al (2015) who showed that salinity reduced the fresh and dry weight of plants. Deficiency in dry and fresh biomass at higher concentration might be due to poor absorption of water from the growth medium due to physiological drought (Ramezani et al, 2011).…”
Section: Resultssupporting
confidence: 88%
“…1a and Table 2). Salinity, in usual case has the inhibitory impact on germination of seeds in wheat, (Zhang et al, 2013) in oat species and (Dheeba et al, 2015) in black gram. The cultivar UPO-212 exhibited highest germination percentage at all levels of salinity inclusive control, but the lowest reduction was achieved by cultivar NDO-2 in all treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Cr deposition in agricultural soils is a global concern as it is non-biodegradable and adversely affects plant growth by decreasing photosynthetic pigments, which results in decreased productivity [8][9][10][11]. Cr is classified as a non-essential metal as it does not have any major biological functions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Cr is the main center of attention as it has a toxic effect on crops grown in contaminated soils (Dhal et al , Khan et al ). It has been widely documented that Cr toxicity causes a decline in plant growth and yield parameters and reduces photosynthetic pigments, stomatal conductance (gs), photosynthetic rate (Pn), transpiration rate (E), water‐use efficiency (WUE) and protein and water contents in plants (Singh et al , Ali et al , Dheeba et al , Gill et al , Hussain et al ). In addition, excess Cr causes oxidative stress by enhancing the generation of reactive oxygen species (ROS), such as electrolyte leakage (EL), hydrogen peroxide (H 2 O 2 ) and malondialdehyde (MDA) in different parts of the plant (Tang et al , Ali et al ).…”
Section: Introductionmentioning
confidence: 99%